AB0803 EFFICACY OF TILDRAKIZUMAB IN PsA: DAS28-CRP SCORES THROUGH WEEK 52. (2nd June 2020) - Chohan, S.; Kavanaugh, A.; Strand, V.; Chou, R. C.; Mendelsohn, A. M.; Rozzo, S.; Mease, P. J.
Abstract : Background: Tildrakizumab (TIL), an anti–interleukin (IL)-23p19 monoclonal antibody, is approved in the US, EU, and Australia for treatment of moderate-to-severe plaque psoriasis. 1 A randomised, double-blind, placebo-controlled, multiple-dose, phase 2b study (NCT02980692 ) evaluating efficacy and safety of TIL for treatment of psoriatic arthritis (PsA) was recently completed. Objectives: To evaluate the effect of TIL in PsA, using the DAS28-CRP responses up to week (W)52. Methods: Patients (pts) ≥18 years old with PsA 2 and ≥3 tender and ≥3 swollen joints were randomised 1:1:1:1:1 to receive TIL (200 mg once every 4 weeks [Q4W], 200 mg every 12 weeks [Q12W], 100 mg Q12W, or 20 mg Q12W) or placebo (PBO Q4W) to W24. Thereafter, PBO Q4W and TIL 20 mg Q12W arms crossed over to TIL 200 mg Q12W to W52. DAS28-CRP was shown to be reliable in PsA studies, 3 and pts achieving scores <3.2 satisfied responder criteria. Adverse events (AEs), including treatment-emergent AEs (TEAEs) and serious AEs (SAEs), were monitored throughout the study. Results: Overall, 391/500 pts screened met the inclusion criteria; 55% were female with a mean age of 48.8 years. At baseline, disease characteristics were generally consistent across treatment arms (Table ). At W24, DAS28-CRP response rates increased across all TIL treatment arms relative to PBO (Figure ). After W24, response rates continued to increase and were sustained through W52, including in pts who switched from PBO to TIL. From W0–W24/W25–W52, 50.4%/39.9% and 2.3%/1.0% of pts experienced a TEAE and SAE, respectively. There were no reports of candidiasis, inflammatory bowel disease, major adverse cardiac events or elevated liver enzymes. From W0–W24, 1 pt (0.3%) had urinary tract infection (TIL 100 mg Q12W). From W25–W52, 1 pt (0.3%) had an intraductal proliferative breast lesion (TIL 20→ 200 mg Q12W). One pt (0.3%) discontinued before 24 weeks due to hypertension. No deaths were reported. Conclusion: Treatment with all doses of TIL increased the rate of DAS28-CRP responders in pts with active PsA and was well tolerated, suggesting a reduction in PsA-related disease activity for up to 52 weeks of treatment. Ongoing analyses will assess whether DAS28-CRP responses correlate with baseline clinical characteristics. References: [1]Reich K, et al. Lancet . 2017;390(10091):276−88. [2]Taylor W, et al. Arthritis Rheum . 2006; 54(8):2665−73. [3]Fransen J, et al. Ann Rheum Dis . 2004; 62:151. Disclosure of Interests: Saima Chohan Employee of: Partner/physician at Arizona Arthritis and Rheumatology Associates, Arthur Kavanaugh Grant/research support from: AbbVie, Amgen, Eli Lilly, Novartis, Janssen, Pfizer, Gilead, UCB, Consultant of: AbbVie, Amgen, Eli Lilly, Novartis, Janssen, Pfizer, Gilead, UCB, Vibeke Strand Consultant of: AbbVie, Amgen, Biogen, Celltrion, Consortium of Rheumatology Researchers of North America, Crescendo Bioscience, Eli Lilly, Genentech/Roche, GlaxoSmithKline, Hospira, Janssen, Merck, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Sanofi, UCB, Richard C Chou Consultant of: Sun Pharmaceutical Industries, Inc, Alan M Mendelsohn Shareholder of: Johnson and Johnson, Employee of: Sun Pharmaceutical Industries, Inc, Stephen Rozzo Employee of: Sun Pharmaceutical Industries, Inc, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau